Kansas - McCrea, McLeod Wilson (My University, 1893)
Introduction: No one wonders than so well a developed agricultural state as ours should have an agricultural college; but a great many persons are surprised that anyone should attend such a college. Kansas people are always surprising the rest of the world; they are always doing what no one else would ever think or care or dare to do.
Citation: McCrea, McLeod Wilson. Kansas. Senior thesis, Kansas State Agricultural College, 1893.
Morse Department of Special Collections
Keywords: Kansas; Agriculture; College; Theses; Manuscripts (documents)